Can Chinese Families Achieve a Low-Carbon Lifestyle? An Empirical Test of China’s Low-Carbon Pilot Policy - Sun, Xuetao; Wang, Zhenhua (Frontiers in Energy Research, 2021)
Global warming has caused concern among countries worldwide. Since 2010, the Chinese government has implemented low-carbon pilot policies (LCPPs) in some regions to control carbon emissions. To evaluate the implementation effects of the LCPPs, we matched China's macro data with Chinese household financial survey data. Specifically, we used a OLS model for assessing the impact of LCPPs on China's household carbon emissions and conducted heterogeneous analysis. Further, we evaluated the mechanism through which LCPPs affect the carbon emissions of Chinese households. The research results yielded three main findings. (1) LCPPs can promote a reduction in household carbon emissions; however, the impact of LCPPs on household carbon emissions exhibits a time lag. (2) LCPPs reduce household carbon emissions by promoting the upgradation of the household consumption structure. The LCPP enables households to reduce consumption of products involving high levels of carbon emissions, while increasing consumption of low-carbon emission products, thereby affecting total household carbon emissions. (3) An analysis of household heterogeneity revealed that LCPPs mainly affect household carbon emissions in the country's eastern and central regions, especially urban households' carbon emissions. This paper describes the implementation effects of LCPPs and suggests a viable path for the further implementation of LCPPs.